Who was William Shakespeare? - Mannis, Celeste Davidson (Who was-- ?, 2006)
Presents a brief profile of the life and works of sixteenth-century playwright, William Shakespeare; and contains black-and-white illustrations that include a diagram of the Globe Theater.